Nutrition and psychiatric disorders: an evidence-based approach to understanding the diet-brain connection - Mohamed, Wael Mohamed Yousef (Springer, 2024)
The book explores the intricate relationship between nutrition, brain function, and psychiatric disorders. The first section of the book delves into the neurobiological aspects of psychiatric disorders, including the neuroanatomy, neuropathology, biochemical and neuropharmacology factors that play a role in the development of these disorders. It also discusses the impact of human nutrition on brain function and the implications of nutrition and metabolism on psychological functioning. The next section focuses on the diet-brain connection, exploring nutritional psychiatry and the current state of evidence, the role of the microbiome, and the effects of certain foods such as chocolate and coffee on mood and mood disorders. The chapters also examine the impact of diet on mental health and cognition across the lifespan and provides a case study of the relationship between diet and psychological health. In the final section, the book delves into the nutritional treatment of psychiatric disorders, including the psychopharmacology of psychiatric disorders and food intake, and multidisciplinary approaches to psychiatric treatment.. Overall, this book offers a comprehensive and evidence-based examination of the complex relationship between nutrition, brain function, and psychiatric disorders, and provides a foundation for further research and development of effective nutritional interventions for the treatment of these disorders.